Emerging tyrosine kinase inhibitors for head and neck cancer. (3rd July 2022) - Long, Zhen; Grandis, Jennifer R.; Johnson, Daniel E.
ABSTRACT: Introduction: Conventional regimens for head and neck squamous cell carcinoma (HNSCC) are limited in efficacy and are associated with adverse toxicities. Food and Drug Administration (FDA) approved molecular targeting agents include the HER1 (EGFR)-directed monoclonal antibody cetuximab and the immune checkpoint inhibitors nivolumab and pembrolizumab. However, clinical benefit is only seen in roughly 15–20% of HNSCC patients treated with these agents. New molecular targeting agents are needed that either act with monotherapeutic activity against HNSCC tumors or enhance the activities of current therapies, particularly immunotherapy. Small-molecule tyrosine kinase inhibitors (TKIs) represent a viable option toward this goal. Areas covered: This review provides an update on TKIs currently under investigation in HNSCC. We focus our review on data obtained and trials underway in HNSCC, including salivary gland cancers and nasopharyngeal carcinomas, but excluding thyroid cancer and esophageal cancer. Expert opinion: While some emerging TKIs have shown clinical benefit, the positive effects have, largely, been modest. The design of clinical trials of TKIs has been hampered by a lack of understanding of biomarkers that can be used to define patient populations most likely to respond. Further preclinical and translational studies to define biomarkers of TKI response will be critically important.